Editorial: Special Issue on the "Molecular Biology of Disease Vectors" - Kotsyfakis, Michail (International journal of molecular sciences, 2023)
Arthropod disease vectors not only transmit malaria but many other serious diseases, many of which are, to a greater or lesser degree, neglected [...].
Keywords: členovci - vektory; molekulární biologie; malárie; infekce přenášené vektorem; Disease Vectors; členovci; Animals; Malaria; Humans; Arthropods; Molecular Biology; lidé; Arthropod Vectors; zvířata